O papel da visão baseada em recursos (VBR) na formulação das estratégias : o caso das industrias de confecção do vestuário de Sarandi-RS - Palma, Aline (2016)
This study has the general objective to understand how the garment manufacturing industries in the city of Sarandi, Rio Grande do Sul, formulate their strategies considering the basis of tangible and intangible assets. To this end, they were defined as specific objectives: identify and how strategies are formulated in industries; identify tangible and intangible resources to achieve the strategy; assess how the industries allocate resources towards the achievement of competitive advantages; and assess the strengths and difficulties in the strategic allocation of these resources. The main reason for the development of this study is that the theory of Resource Based View still has room and need to advance in the theoretical and empirical, including Brazil. In addition to lack of studies relating the theme with the process of formulating strategies in the garment industry context. To build the foundation of this research were addressed in the literature review, competitiveness issues, strategy and its formulation process, types of strategies and the theory of VBR. At the end of the literature review, we present a systematization of all content explored in this section, in order to guide the search. In the case of methodological procedures used, as the approach, the research is part of a qualitative and goal, is delimited the study as exploratory. Being the technical procedure employed the case study. The collected data are primary and secondary sources. The collection of primary data were collected through interviews with owners of three industries in the production of Sarandi sector. The interview script was developed from the extracted categories of analysis of literature review, reflecting also the specific objectives of the study. The analysis of the data given by the content analysis method. It was observed that the process of formulating strategies in industries has informal and emergent character. It was possible to identify schools of strategic thinking, entrepreneurial, environmental, design, planning and learning in the process of formulating the strategy, each industry reflected their particular characteristics in different schools. As for features, it is believed that taking them into account is greatly strategic to the competitiveness of the surveyed industries and also that intangible resources have greater ability to generate competitive advantage. Furthermore, the perception of two interviewed industries, these do not have competitive advantage, but factors that assist in their competitiveness. Only one company believes that its brand has the ability to generate competitive advantage. Through the analysis of the collected data, it is understood that some resources exploited by companies may be able to provide competitiveness for the company in the market in which they operate, but do not achieve a sustainable competitive advantage.